2014
DOI: 10.2147/ijn.s50742
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of bone morphogenetic protein-2 and substance P using graphene oxide for bone regeneration

Abstract: In this study, we demonstrate that graphene oxide (GO) can be used for the delivery of bone morphogenetic protein-2 (BMP-2) and substance P (SP), and that this delivery promotes bone formation on titanium (Ti) implants that are coated with GO. GO coating on Ti substrate enabled a sustained release of BMP-2. BMP-2 delivery using GO-coated Ti exhibited a higher alkaline phosphatase activity in bone-forming cells in vitro compared with bare Ti. SP, which is known to recruit mesenchymal stem cells (MSCs), was co-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 41 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, there was no significant difference in the new bone density between the control and HAp grafts. Recently it was reported that GO-coated titanium implants can be used for the dual delivery of both BMP-2 and substance P, and that this delivery promotes bone formation in a mouse calvarial defect model 66 . Although not applied in combination with BMPs, the rGO/HAp graft in the form of a paste implanted into the calvarial defect is believed to promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there was no significant difference in the new bone density between the control and HAp grafts. Recently it was reported that GO-coated titanium implants can be used for the dual delivery of both BMP-2 and substance P, and that this delivery promotes bone formation in a mouse calvarial defect model 66 . Although not applied in combination with BMPs, the rGO/HAp graft in the form of a paste implanted into the calvarial defect is believed to promote osteogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effects of chitosan on bone healing have been demonstrated in several in vitro and in vivo studies 33 , while graphene oxide has been used to enhance bone healing and to accelerate the regeneration and osteointegration of biomaterials, such as hydroxyapatite 34 , ß-tricalcium phosphate 20 , titanium implants 35 . However, to the best of our knowledge, the combined effect of chitosan and graphene oxide on bone defects has not been explored in vivo before.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cellular attachment, proliferation and bone-mineralization related activities were enhanced in cells grown on the MrGO. In addition, based on the protein adsorption capability, GO can be utilized for the delivery of bone morphogenetic protein-2 (BMP-2) and substance P (SP) through electrostatic interaction between the ionized groups of GO and proteins and hydrophobic π-π stacking [171]. …”
Section: Applications In Tissue Engineering and Regenerative Medicinementioning
confidence: 99%